EFFECT OF HYPOTHALAMIC PREOPTIC NUCLEUS ELECTRICAL ACTIVITY CHANGES ON GONADAL HORMONE REGULATION IN NORMAL AND EXTREME STATES - Eminova, G.A.; Ismayilov, Yu.B.; Rustamova, T.V.; Veliyeva, Z.Y.; Jafarova, A.M.; Kerimova, T.H.; Gasimzade, T.N. (World of Medicine and Biology, 2025)
With the purpose to examine the changes in the activity of gonadal hormones resulting from the effects of hydrogen sulfide gas and electrode implantation on the preoptic nucleus of the hypothalamus 35 female rabbits were observed. The activity of follicle-stimulating hormone, luteinizing hormone, and estradiol in the blood were evaluated after stress. On the 5th day follicle-stimulating hormone decreased by 0.26 IU/l; luteinizing hormone decreased by 0.18 IU/l, estradiol increased by 207.4 pg/ml (P